Appendix to the article “Enablers and Obstacles in IWRM Implementation and their Contributions to Sustainable Territorial Development" - Gallegos Monteagudo, Armando (2026)
The dataset constructed for this study comprises 375 peer-reviewed empirical articles that analyze the implementation of Integrated Water Resources Management (IWRM) across diverse geographical and institutional contexts. It was systematically developed by the authors through a structured process of review and coding, identifying the key enablers and obstacles reported in each study. The resulting dataset constitutes a comparative analytical resource that synthesizes international evidence accumulated over more than two decades and aims to enhance transparency, methodological traceability, and replicability. The dataset is organized into three interconnected components. The first component, Database, contains the main corpus of analyzed articles and their general characteristics and corresponds to “Enablers and Obstacles in IWRM Implementation and their Contributions to Sustainable Territorial Development”. The second component, Enablers, presents the enablers identified in IWRM implementation studies. The third component, Obstacles, presents the obstacles identified in IWRM implementation studies.